A BRIEF SURVEY ON UNDERWATER WIRELESS OPTICAL COMMUNICATION SYSTEM - Kakati, Amayika; Sharma, Deeksha; Aggarwal, Nikhil N (International Journal of Research -GRANTHAALAYAH, 2018)
The underwater wireless optical communication (UWOC) system gives very high rate of underwater data transmission over several meters. It utilizes the visible band in the spectral range of 390-750nm of the electromagnetic spectrum. In this paper, we study various types of link configurations depending upon the circumstances in water environment. We also study the effect of various water types on the system performance. We find that the UWOC system is affected especially by inherent optical properties such as absorption and scattering and the effect of these properties is different in various water types. We also present that misalignment in UOWC system adversely affects its functioning and reliability. Finally, we present that hybrid system design for a proper systematic UOWC system.